Peningkatan Kreativitas dan Keterampilan Digital Pemuda Karang Taruna Kampung Karasak - Wibowo, Agung Toto; Fahlena, Hilda; Maharani, Warih; Ramadhan, Nur Ghaniaviyanto (Madani : Indonesian Journal of Civil Society, 2025)
Karasak Village, Ciheulang Village, Ciparay District, Bandung Regency, still faces challenges, including low digital literacy and limited use of information technology to support the development of the village's potential. This condition has implications for the limited ability of the younger generation to produce and distribute creative content that can strengthen local identity and increase village competitiveness in the digital realm. To address these challenges, the community service team implemented a training program targeting Youth Karang Taruna on December 15, 2024. The training materials were comprehensively designed, covering the use of social media, talent modules, storytelling, on-camera communication, video shooting techniques, and music and video editing. The method employed was a combination of theoretical instruction, direct practice, and interactive mentoring, enabling participants to produce digital content products independently. Evaluation of the activity was conducted through the distribution of questionnaires, with the results showing that 94% of participants agreed or strongly agreed with the usefulness of the training. These findings confirm that the activity was effective, well-received by participants, and has the potential to encourage increased digital literacy capacity and creativity of youth in creating content based on local potential, ready for publication on social media.